Preliminary development of radioscopy detector for specific industrial radiography inspection - Khairul Anuar, Mohd Salleh; Ab. Razak, Hamzah; Shaharudin, Sayuti; Siti Madiha, Muhammad Amir; Noorhazleena, Azaman; Sapizah, Rahim; Abd. Nassir, Ibrahim (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.